Pengaruh Lokasi, Keragaman Produk, dan Brand Image Terhadap Loyalitas Nasabah Tabungan Pada Kantor Pusat PT. BPR Jwalita Trenggalek (Perseroda) - Tyas Ajeng Puspitaningrum; Aprilia Dian Evasari; Beny Mahyudi S (Master Manajemen, 2025)
This study aims to examine the influence of location, product variety, and brand image on savings customer loyalty at the Head Office of PT. BPR Jwalita Trenggalek Perseroda. Customer loyalty is a crucial factor for the sustainability of a banking institution, as loyal customers not only continue to use banking services but also tend to recommend them to others, thereby contributing to long-term growth. The variables examined in this study—location, product variety, and brand image—were chosen because they represent essential aspects that can strengthen the relationship between customers and the bank. This research employed a quantitative approach to ensure objectivity in data collection and analysis. The primary data were gathered through observation, interviews, and structured questionnaires distributed to savings customers of the bank, while secondary data were obtained through a literature review. The analytical techniques applied included validity and reliability testing to ensure the accuracy and consistency of the instruments, classical assumption tests to meet regression requirements, and multiple linear regression analysis to measure the influence of each independent variable on the dependent variable. Furthermore, hypothesis testing was conducted using the t-test and F-test, complemented by the coefficient of determination to measure the explanatory power of the model. The findings reveal that: (1) location has a significant effect on customer loyalty, indicating that accessibility and convenience play a vital role in customer decisions to remain loyal; (2) product variety significantly influences customer loyalty, demonstrating that diverse and innovative savings products attract and retain customers; and (3) brand image also has a significant effect on customer loyalty, suggesting that trust and positive perceptions toward the bank strengthen long-term relationships. Finally, the study confirms that location, product variety, and brand image simultaneously exert a significant effect on customer loyalty. These results underscore the importance for banking institutions to continuously improve service accessibility, diversify financial products, and build a strong brand image in order to enhance customer loyalty and maintain competitiveness in the financial services industry.